PERUBAHAN KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PASCA KONFLIK POSO (Studi Kasus Pengungsi Poso di Desa Wuasa Kecamatan Lore Kabupaten Poso) - , UCI LUSIANA NYOLONYOLO, S.Sos, Drs. Soetomo, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
All people can experience the transformation process, either in individual phase (micro), groups in a society (meso) or in a society itself as a wide group unity (macro). Therefore, the transformation process can be derived naturally or by plan. In terms of the transformation process experienced by some people in Poso regency, it can be classified into a non-planned transformation since the endless social conflict started from 1998 and its climax on 2000. In fact, there were much physical and mental violence, the expropriation of the inhabitantâs socio-economics rights, people lived in fear and it gave an impact of the obstruction and discontinue of socio-economics activity. This condition got worst since there was no insurance from government concerning on life safety, therefore, it caused the exodus of people in the more saving place. The research is conducted to know the daily activity of refugee in fulfilling their basic needs as well as their disposition in new society stratification in Wuasa Village. Thus, the research uses qualitative â deductive analysis to explore in depth and comprehend as well as explain the phenomenon occurred. The data used is derived from refugee or society of Wuasa Village as primary data source and the stakeholder comprising of government, NGO or public figures. Moreover, it uses documents as secondary data source. Those data are achieved through observation, a depth interview and documentation related on and sutain in theis research theme. Living in asylum is different from the previous condition. It lives with the shortage and they have to start from the beginning so that their life pattern is changed in term of fulfilling their basic needs. This condition is worst because the socio-economics condition of the refugee is in declining vertically mobility (social sinking), either in economics or in social condition. In addition, there are differences of value, norm, culture and point of view as well as interest of the refugee and local inhabitant of Wuasa Village. It is as reality requiring adjustment/adaptation and interaction, yet several similarities such as religion of refugee and local inhabitant can decrease those differences (cross cutting), thus, the recent fact is that the refugee is back to live normal and places in all socio-economics strata of Wuasa Villageâs society. In the arrangement process of the refugeeâs socio-economics condition to live normal, there are some roles of stakeholder consisting of government, religion figure and public figure, even it has not maximal, yet and it is not suitable with the necessity. The transformation condition of socio-economics of refugee above can be explained deeply in a research that the writer conducted and explained in this thesis.